Status and distribution in Peru of the Black-Billed Mountain-Toucan Andigena nigrirostris (Waterhouse, 1839) - Salazar, Sonia (2017)
In Peru Andigena nigrirostris is considered hypothetical due to the absence of published records. To date ten specimens have been collected and two sound records and a photograph of a free-flying individual have been obtained. The latter record was from a protected area in Peru, the Santuario Nacional Tabaconas Namballe. Records indicate that this species is distributed in the montane forests of the eastern slope, north of the Huancabamba depression, between ~ 2200 a 2900 m elevation.